Transforming lives and societies through education and research at DCU - Samantha Fahy MSc MBA; Caroline Moran MSc (Universitas Diponegoro, 2022)
Dublin City University identifies Sustainability as a core theme underpinning all of the University’s activities and strategic goals [1]. DCU is committed to ensuring that all graduates understand the challenges of environmental sustainability and have the sustainability competencies that will equip them to be global citizens, inspired and empowered to take the actions necessary for a sustainable future. DCU undertakes sustainability focused research and works to demonstrate, where feasible, these sustainable solutions within our Living Lab campuses. DCU also works with enterprise and societal communities to engage, inform and support these communities on our joint sustainable journey.Keyword: Sustainability Challenges, Education for Sustainable Development, Environmental Sustainability